Pengaruh Relaksasi Otot Progresif Terhadap Kualitas Tidur Lanjut Usia Di Panti Jompo Aisiyah Surakarta - Putri, Riski Sandi, Umi Budi Rahayu, SSt. Ft. SPd. M. Kes (2017)
Background: Elderly people tend to decrease the quality of sleep. This occurs as a result of certain biological changes such as the loss of control of circadian rhythms in the sleep process. Lack of sleep can lead to daytime sleepiness,memory impairment, depression, cognitive disorders, stress, frequent falls and loss of quality of life. Decreased quality of sleep can be resolved with progressive muscle relaxation therapy. Objective: This study aimed to investigate the effect of progressive muscle relaxation on the quality of sleep of the elderly in a nursing home Aisyiyah Surakarta. Methods: This study is a Quasi Experiment experimental approaches and methods pretest-posttest control group Design. responding this study of 20 elderly people who were divided into two groups: 10 people treated group (progressive muscle relaxation) and 10 control group (without therapy). Research carried out for 4 weeks, and every night before bed. Quality of sleep before and after the progressive muscle relaxation therapy was measured by a questionnaire PSQI. Data analysis using Paired Sample T Test and Test Independent Sample T Test. Result: The test results influence the dependent group pre and post test progressive muscle relaxation was obtained p-value 0.0001 then there is the effect of progressive muscle relaxation on the quality of sleep of elderly. While the influence of different test independent pre and post test was obtained p-value of 0.0001, so it is concluded that there are differences in improving the quality of sleep of the elderly in the treatment group and the control group. Conclusion: The provision of progressive muscle relaxation is proven to improve the quality of sleep of elderly compared with no therapy.